Mechanical thrombectomy with intra-arterial alteplase provided better functional outcomes for AIS-LVO: a meta-analysis - Yang, Xingyu; Wang, Zilan; Chen, Huiru; Qiu, Youjia; Teng, Haiying; Chen, Zhouqing; Wang, Zhong; Chen, Gang (Frontiers in Neuroscience, 2023)
Background Several clinical trials have shown that intra-arterial thrombolysis using alteplase during mechanical thrombectomy (MT) has a better outcome than MT alone in ischemic stroke management. We performed the current meta-analysis to estimate the efficacy and safety of MT with intra-arterial alteplase therapy. Methods The MEDLINE, Embase, Cochrane Library, and ClinicalTrials.gov databases were searched up to Mar. 2022 to identify the clinical trials that compared MT alone versus MT with intra-arterial alteplase therapy. STATA 16.0 was used for statistical analysis. The odds ratios (ORs) and 95% confidence intervals (95%CIs) were calculated with a random effect model. Results Seven studies involving 1,083 participants were included. The primary outcomes were better functional outcomes, defined as a modified Rankin Scale (mRS) score between 0 and 2 at 90 days, and successful recanalization, defined as a modified thrombolysis in cerebral infarction (mTICI) score ≥ 2b. Compared to MT alone, MT with intra-arterial alteplase did not lead to higher mTICI scores (OR 1.58, 95%CI 0.94 to 2.67, p = 0.085, I2 = 16.8%) but did lead to better mRS (OR 1.37, 95%CI 1.01 to 1.86, p = 0.044). There was no increase in mortality or bleeding events in the overall or subgroup analyses. Conclusion MT with intra-arterial alteplase did not improve the recanalization rate but provided better functional outcomes. The intervention did not increase adverse effects in any subgroup at the same time. Clinical trial registration http://inplasy.com, identifier INPLASY202240027.